Demystifying non-invasive approaches for screening jaundice in low resource settings: a review - Abiha, Umme; Banerjee, Dip Sankar; Mandal, Saptarshi (Frontiers in Pediatrics, 2023)
All national and international pediatric guidelines universally prescribe meticulous bilirubin screening for neonates as a critical measure to mitigate the incidence of acute bilirubin encephalopathy (ABE) and Kernicterus. The prevailing gold standard for jaundice detection in neonates necessitates invasive blood collection, followed by subsequent biochemical testing. While the invasive procedure provides dependable bilirubin measurements and continues to be the sole gold standard diagnostic method for assessing bilirubin concentration. There exists a pressing need to innovate non-invasive screening tools that alleviate the sampling stress endured by newborns, mitigate iatrogenic anemia, and expedite the turnaround time for obtaining results. The exploration of non-invasive modalities for bilirubin measurements is gaining momentum, driven by the overarching goal of minimizing the number of pricks inflicted upon neonates, thereby rendering screening a swift, efficient, comfortable, and dependable process. This comprehensive review article delves extensively into the array of non-invasive approaches and digital solutions that have been proposed, implemented, and utilized for neonatal bilirubin screening, with a particular emphasis on their application in low-resource settings. Within this context, the review sheds light on the existing methodologies and their practical applications, with a specific focus on transcutaneous bilirubin meters. Moreover, it underscores the prevailing open challenges in this domain and outlines potential directions for future research endeavors. Notably, the review underscores the imperative need for robust educational programs targeted at both families and healthcare personnel to expedite the process of seeking timely care for neonatal jaundice. Additionally, it underscores the necessity for the development of enhanced screening and diagnostic tools that can offer greater accuracy in clinical practice.